Editor’s note: - Sebolai, Kabelo (Journal for Language Teaching, 2024)
This volume follows a landmark special issue of the Journal for Language Teaching dedicated to articles written in African languages. It comprises a total of six articles written in English and one in isiZulu that continue to deal with matters that are pertinent to the issue of language teaching and development in current times. We continue to be grateful to the authors of these articles for choosing the Journal for Language Teaching as the destination for their scholarly work. The same goes for the scholars who agreed to review these articles and provided feedback which guided our decision to include them in this issue.